The Bolar exception: Legislative models and drafting options - Carlos María Correa (South Centre, 2016)
The basic principle of patent law is that once the term of a patent has expired, the protected subject matter becomes a part of the public domain. Hence, it can be freely used, including for commercial purposes, without the interference by the former patent owner. This allows competitors to enter the market immediately after such expiry, eventually leading to lower prices for consumers and welfare gains. Pharmaceutical products, however, cannot be marketed without prior authorization of the competent regulatory agency. Such authorization is conditional upon the submission and approval of an application that normally has to be accompanied with certain pieces of information. Regulatory requirements differ among countries. Despite some efforts towards harmonization, there is considerable diversity in respect of what evidence is required, the applicable procedures, and how long it can take to obtain the approval. The interface between the regulations for marketing approval of medicines and patent law explains the need for what has been termed as the "early working" or "Bolar exception" (hereinafter Bolar exception). If a producer of a generic or similar version is bound to wait until the last day of the term of patent(s) covering a pharmaceutical product, the owner of expired patent(s) will enjoy a de facto additional period of monopoly power, as long as a generic version of the product obtains market permission from the regulatory authority. During this period there can be no competition and, hence, the owner of the expired patent may continue to charge a monopolistic price. Since governments and consumers would benefit from lower prices as the result of generic competition, the Bolar exception may play an important role in reducing the burden on health budgets and increase access to more affordable pharmaceuticals.
Keywords: 300; Arzneimittel; Außenhandel; TRIPS; Arzneimittelrecht; Rechtsdurchsetzung; Welt